2020
DOI: 10.3389/fchem.2020.00716
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Activated Delayed Fluorescence: Beyond the Single Molecule

Abstract: Emitters that exhibit thermally activated delayed fluorescence (TADF) are of interest for commercial applications in organic light-emitting diodes (OLEDs) due to their ability to achieve internal quantum efficiency of 100%. However, beyond the intrinsic properties of these materials it is important to understand how the molecules interact with each other and when these interactions may occur. Such interactions lead to a significant red shift in the photoluminescence and electroluminescence, making them less pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 82 publications
0
20
0
Order By: Relevance
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…Thus, more and more scientists have devoted themselves into the research of it in recent years. [82][83][84][85][86][87][88][89][90][91] Especially, Ruren Xu and coworkers proposed "Towards a new discipline of condensed matter chemistry" in 2018. [82,83] It is believed that after constant exploration, the molecular structure-packing property relationship could be revealed clearly and the adjustment of luminescence property in aggregation state could be easily realized from the source of molecular design.…”
Section: Summary and Perspectivesmentioning
confidence: 99%
“…The exciplex formation between the host and the TADF emitter is an issue that should be taken into account. [127] As discussed, the purely organic TADF emitters are typically constructed based on a donor-acceptor structure. In this context, exciplex formation between the donor of the host and the acceptor of the TADF emitter (vice versa) is possible in the solid film, whether the host is unipolar or bipolar.…”
Section: Exciplex Formation Between the Host And Tadf Emittermentioning
confidence: 99%
“…[20] In recent TADF literature on novel materials, a common motif is observed at higher emitter concentrations, the emission spectrum redshifts. [13] Contrasting explanations have been offered for the archetypical TADF emitter 1,2,3,5-tetrakis(carbazol-9-yl)-4,6-dicyanobenzene (4CzIPN), [1] which shows a similar redshift feature. Kim et al suggested that the observed effect is due to SSSE, [15] while Etherington et al followed up the study and revealed that dimer formations are the more likely reason.…”
Section: Steady-state Spectra and Plqymentioning
confidence: 99%
“…[ 20 ] In recent TADF literature on novel materials, a common motif is observed at higher emitter concentrations, the emission spectrum redshifts. [ 13 ] Contrasting explanations have been offered for the archetypical TADF emitter 1,2,3,5‐tetrakis(carbazol‐9‐yl)‐4,6‐dicyanobenzene (4CzIPN), [ 1 ] which shows a similar redshift feature. Kim et al.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
See 1 more Smart Citation